2010
DOI: 10.1007/s10943-010-9396-x
|View full text |Cite
|
Sign up to set email alerts
|

Communicating HIV/AIDS Through African American Churches in North Carolina: Implications and Recommendations for HIV/AIDS Faith-Based Programs

Abstract: This study explores HIV/AIDS communication strategies among church leaders at predominately African American churches in a metropolitan city and surrounding areas in North Carolina. The church leaders contacted for the study are members of an interfaith-based HIV/AIDS program. The researchers used semi-standardized interviews to explore how church leaders address HIV/AIDS in the church. The findings indicate that the seven church leaders who participated in the study use a variety of communication channels to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…These leaders can instill feelings by persons living with HIV that support from God is important to their lives, especially in times of difficulty. Like Moore et al (2010), we found that many religious leaders were committed to providing a caring environment for people with or at risk for HIV=AIDS. In addition, many focus group participants expressed wanting and needing that safe space, citing the presence of God and religion as sources of the kind of support and care that they needed to take better care of themselves.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These leaders can instill feelings by persons living with HIV that support from God is important to their lives, especially in times of difficulty. Like Moore et al (2010), we found that many religious leaders were committed to providing a caring environment for people with or at risk for HIV=AIDS. In addition, many focus group participants expressed wanting and needing that safe space, citing the presence of God and religion as sources of the kind of support and care that they needed to take better care of themselves.…”
Section: Discussionmentioning
confidence: 82%
“…Religious involvement has been found to be associated with lowered levels of distress (Prado et al, 2004;Simoni & Ortiz, 2003) and increased physical health and long-term survival (Ironson & Kremer, 2009;Morse et al, 2000), among people living with HIV=AIDS. For these reasons, public health officials and religious leaders have begun to work together to implement faith-based approaches to reduce HIV=AIDS and respond to the needs of people living with the virus (Francis & Liverpool, 2009;Moore, Onsomu, Timmons, Abuya, & Moore, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have the potential to be spaces for critical dialogue on HIV/AIDS. Churches can be sites to develop competence and act as receptive social spaces because of the power they may already hold in the community (Moore et al, 2012).…”
Section: The Church's Role In African American Women's Daily Livesmentioning
confidence: 99%
“…The management entails an involved mediation process-with media, environments and networks through which symbols and expressions of faith are circulated and coalitions/partnerships are built. 77 Certain 'programmatic and systemic effects' result from the infusion of RKM as a player/ social actor-having consequences for the profile of service and who gets served. This in effect influences the transferability of RKM interventions across religious and secular applications in order to satisfy constitutional issues of equity and public choice.…”
Section: What Rkm's Seva Means For the Indian Social Fabric: Discussimentioning
confidence: 99%